Conservation of the Land Walls Protection Area by Renewal (!): Evaluating the Spatial Effects of the Law No. 5366 Through Zeytinburnu Culture Valley Project of Istanbul - Durusoy Ozmen, Elifnaz; Can, Mehmet Cengiz (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2018)
The urban transformation process accelerated immensely by the end of the 20th century is one of the problems Turkey has faced. This process, which is guided by various legal and administrative sanctions for many years, affects historical urban areas negatively. One of these sanctions providing a basis for inappropriate interventions on the historical urban areas is the Law No. 5366 on Conservation by Renovation and Use by Revitalization of the Deteriorated Historical and Cultural Immovable Property. This law, the Renewal Law in short, carried into effect in 2005, causes irreversible damages and losses through the renewal of the qualified urban sites. The purpose of this study is to critically evaluate the urban transformation of the Land Walls Protection Area, one of four sites determined as world heritages in the Historical Peninsula of Istanbul, through a reading of the Law No. 5366.This evaluation is made throughZeytinburnu Culture Valley Project, which is the largest renewal project identified among the six renewal zones falls within the Land Walls Protection Area.The paper begins with the history of Zeytinburnu through a chronological narration. After emphasizing the values of the district,Zeytinburnu Culture Valley Project is introduced in terms of its purpose, scope and content. The study then focuses on the spatial effects of Law No. 5366 through the final state of the project. Lastly, on its 13th year of force, the consequences of the Renewal Law on the cultural heritage that needs to be protected are specified in the light of the internationally valid charters from a conservation point of view.
Keywords: Conservation; Land Walls Protection Area; Renewal Law No. 5366; urban transformation; Zeytinburnu Culture Valley Project; Architecture